2015
DOI: 10.1002/2015ja021433
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a hot sodium ion population on the growth of the Kelvin‐Helmholtz instability in Mercury's magnetotail

Abstract: Observations of Mercury's local plasma environment by MErcury Surface, Space ENvironment, GEochemistry, and Ranging have revealed that the planet hosts a strongly asymmetric magnetosphere as a result of an off‐axis dipolar or quadrupolar internal field and significant finite Larmor radius effects at the boundary layer between magnetospheric and solar wind plasma environments. One important asymmetry appears in the growth and evolution of Kelvin‐Helmholtz (K‐H) waves at the dawn and dusk flanks of the magnetopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the study showed that the large majority of the KH waves occurred for northward IMF. Different theories explain the asymmetry observed, where two are connected either to an asymmetric mass loading in the velocity shear layer where the KH instability forms [e.g., Anderson et al , ; Sundberg and Slavin , ] or to the finite Larmor radius (FLR) effects and the broadening of the shear layer on the dawnside magnetopause [e.g., Glassmeier and Espley , ; Nakamura et al , ; Gershman et al , ; Gingell et al , ]. However, the asymmetry is still viewed as an open issue, and both theories need to be confirmed by further observations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study showed that the large majority of the KH waves occurred for northward IMF. Different theories explain the asymmetry observed, where two are connected either to an asymmetric mass loading in the velocity shear layer where the KH instability forms [e.g., Anderson et al , ; Sundberg and Slavin , ] or to the finite Larmor radius (FLR) effects and the broadening of the shear layer on the dawnside magnetopause [e.g., Glassmeier and Espley , ; Nakamura et al , ; Gershman et al , ; Gingell et al , ]. However, the asymmetry is still viewed as an open issue, and both theories need to be confirmed by further observations.…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of this is that where usually the planetary atmosphere is an important source of ions, at Mercury the magnetosphere couples directly to the planet's surface which causes the surface to act as both a sink for ions and also a source as ions are sputtered away [Koehn et al, 2002]. These pickup ions, especially the sodium ions, tend to have gyro-radii within an order of the size of the Hermean magnetosphere and therefore kinetic effects become important [Gingell et al, 2015, Trávnícek et al, 2010.…”
Section: Mercurymentioning
confidence: 99%
“…2006; Faganello et al. 2008 a ; Matsumoto & Seki 2010; Leroy & Keppens 2017) or by adopting a hybrid kinetic model but neglecting electron inertia (Gingell, Sundberg & Burgess 2015). In this case, however, the LHDI cannot grow since the FGM scales as (Gary & Sgro 1990), where is the wave number associated to the FGM and the mass ratio between ions and electrons, and stabilizes more and more when the density gradient scale length becomes larger than a few ion inertial lengths (Gary 1993).…”
Section: Introductionmentioning
confidence: 99%